HUBUNGAN JARAK RUMAH KE INSTALASI PENGOLAHAN AIR DENGAN KADAR SISA CHLOR PADA JARINGAN DISTRIBUSI IPA PUCANG GADING PDAM KOTA SEMARANG - Wilujeng Ginanjarwati; Onny Setiani; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Pucang Gading Water Treatment Plant (WTP) is the smallest capacity of PDAM Semarang City which has a wide area, including Sendangmulyo, Klipang, Dinar Mas, Dinar Elok, Meteseh, and Bukit Kencana Jaya. The measurement results by the PDAM from January to March 2018 showed that chlorine residual level at the customer's home of the Pucang Gading WTP distribution is below from the recommended chlorine residual limit (0.2-0.5 mg/l). Decrease in chlorine residual levels also occurs from the WTP to the customer's home. The purpose of this study was to determine the relationship between the distance of the house to the Water Treatment Plant (WTP) with chlorine residual levels in the Pucang Gading Water Treatment Plant distribution in PDAM Semarang City. This research was an explanatory research with a cross sectional study. The sample of this study were 45 customers who were taken based on purposive sampling. Data analysis using Spearman Rank Correlation Test. The results of the measurement of the average chlorine residual level in the customer's home is 0.08 mg/l and the closest distance of the house to the Pucang Gading Water Treatment Plant (WTP) is 150 m with the furthest distance is 6000 m. There is a relationship between the distance of the house to the Water Treatment Plant (WTP) and the chlorine residual level with p value= 0,000 and r count= -0,604. The farther distance of the house to the WTP will affect the decrease in chlorine residual level. So it is necessary to do additional chlorine injection for distant distribution areas from the Water Treatment Plant (IPA).